Cedera Kepala Ringan - Sufia Rahma; Herlina Sari (Jurnal Ventilator, 2024)
Head injury is mechanical trauma to the head, either directly or indirectly, which causes neurological function disorders, which are temporary or permanent physical, cognitive and psychosocial function disorders. The incidence of head injuries in Indonesia in 2018 from 34 provinces in Indonesia reached 11.9% of cases in the last year, mostly due to motorbike traffic accidents. The clinical condition and level of consciousness after a head injury are assessed using the Glasgow Coma Scale (GCS), which can classify head injuries into mild head injuries, moderate head injuries and severe head injuries. The prognosis for head injury patients will be better if management is carried out appropriately and quickly.